The Relationship between the Intensity of Gadget Use and Family Parenting Patterns with the Development of Children 36-72 Months in Sambaliung State Kindergarten - Rahmawati, Sri Isni Novia; Risnawati, Risnawati; Sulistyorini, Chandra; Meihartati, Tuti (Institute Of Computer Science (IOCS), 2024)
Children who are in the early age phase (36-72 months old) are an essential period in the process of developing children's skills and intelligence that will have a major influence on adult life. The high rate of developmental problems in early childhood, especially pre-school age children (36-72 months), is inseparable from various factors that influence it. Among them are caused by environmental exposure (gadgets and parenting patterns) and psychological problems. To know the relationship between the intensity of gadget use and family parenting patterns with the development of 3-6 year old children in Sambaliung State Kindergarten. Quantitative which is associative with a cross sectional approach. the number of samples was 62 children aged 3-6 years with total sampling technique. The instruments used were gadget questionnaires and the PSDQ Questionnaire (Parenting Style Dimensions Questionnaire). BASED on the results of the spearman rank correlation test, the p value is 0.019, where this figure is <0.05, which means Ha is accepted and Ho is rejected, so it can be concluded that there is a relationship between the intensity of gadget use and child development, and based on the results of the spearman rank correlation test, the p value is 0.033, where this figure is <0.05, which means Ha is accepted, so it can be concluded that there is a relationship between family parenting style and child development. There is a relationship between the intensity of gadget use and family parenting with child development